High-power LED characterization - Heng, Celine Si Lin (2014)
The efficiency decreases at high current, is a major problem to solid state lighting. This problem is called “droop”. The definition of droop is the loss of efficiency at high power. In order to keep the electrons in this region, the feature have an electron blocking layer, Gan barriers and active region with InGaN quantum wells. In LEDs, the causes of the droop efficiency, one of the reasons would be heat junction. The heat will give out too much energy to the electrons and which will result the quantum being unable to trap them. This led some of them to escape, unable to recombine and being swept away by electric fields in the device. For electroluminescence spectroscopy, measurements show that efficiency droop found in InGaN/GaN LEDs is related to heat. The light efficiency of LEDs wafers measured, external quantum efficiency shows a strong droop as the current increases. Due to the heat imparts energy to electrons and holes, the quantum wells can no longer store and trap them. Instead of recombining, some of them escape, only to be swept away by the electric fields in the device.Doing a experiment for comparison of DC and Pulse measurement, and results of minimizing droop and improving efficiency is using pulse measurement.